Prevalence of Overweight, Obesity, and Comorbid Conditions Among U.S. and Kentucky Adults, 20002002 - Todd M. Jenkins, MPH (Centers for Disease Control and Prevention, 2005)
Introduction Obesity rates for adults in Kentucky are regularly among the highest in the nation. Since 1991, adult obesity in Kentucky and the United States has nearly doubled. This trend is of great concern because excess weight has been associated with several chronic diseases and conditions. This paper reports on the prevalence of overweight and obesity among adults in Kentucky between 2000 and 2002. The estimates produced by this study will provide baseline figures for developing Kentuckys statewide obesity action plan. Methods A secondary data analysis was performed using the Centers for Disease Control and Preventions Behavioral Risk Factor Surveillance System. Prevalence estimates and odds ratios were calculated for the United States and Kentucky. Results In Kentucky, 24.2% of adults were obese, compared with 21.9% nationally (P < .001). There were also significantly more overweight adults in Kentucky than there were nationwide (P < .001). Logistic regression showed that overweight and obese adults were more likely to report various comorbid conditions. Conclusion Overweight and obesity estimates in Kentucky were significantly higher than nationwide figures. However, overweight/obese adults in Kentucky were no more likely than their U.S. counterparts to report selected